Analisis Risiko Akad Syariah pada Pembiayaan KPR; Studi Perbandingan Akad Istishna, Musyarakah Mutanaqishah, dan Ijarah Muntahiyah Bittamlik - Royyan Ramdhani Djayusman; Fina Nurafni (IAIN Langsa, 2025)
This study aims to analyze and compare the inherent risks in the three main contracts used in Sharia mortgage financing (KPR), namely Istishna, Musyarakah Mutanaqishah, and Ijarah Muntahiyah Bittamlik. This article is categorized as a literature-based study with a qualitative approach. The methodology employed is a normative legal study presented comparatively. The results indicate that each contract has distinct risk characteristics: the Istishna contract faces a high risk of delivery failure, the Musyarakah Mutanaqishah contract is exposed to risks of installment payment delays and top-up requests, while the Ijarah Muntahiyah Bittamlik contract carries lower risks with a simpler structure and flexibility in ownership transfer. These findings provide recommendations for Islamic financial institutions to tailor contract choices according to customer profiles and operational risks in order to enhance the effectiveness and sustainability of Sharia mortgage financing.